ZIF‑8 membrane: the synthesis technique and nanofltration application - Dayang Norafizan, Awang Chee; Farhana, Aziz; Mohamed Afzal, Mohamed Ami; Ahmad Fauzi, Ismail (Springer Nature Switzerland, 2022)
Membrane technology for water treatment is growing due to the increased demand for clean water and the stringent standard for water quality. Nanofltration (NF) is widely used in membranes for water treatment due to lower energy consumption and higher fux rates. The application was not limited to only water treatment, yet NF showed excellent potential for solvent nanofltration application. The utilization of MOF materials for the preparation of NF membranes to produce composite membranes has attracted more attention among researchers due to the advantages ofered by the material. Zeolitic imidazolate framework-8 (ZIF-8) membrane has been considered a promising MOF membrane with its capabilities and promising performance due to the small aperture size of the compounds and the stability towards harsh chemical condition. The purpose of this review is to present the synthesis approaches on the preparation of ZIF-8 membranes and the application of ZIF-8 membrane for NF application. The challenges and prospects of ZIF-8 membranes are also discussed to further stimulate the development and the application of ZIF-8 membrane for NF.